Micro, Small and Medium Enterprises Development in The Post COVID 19 Pandemic: Case Study of MSMEs in Indonesia - Maulana, Hartomi; Astuti, Rahma Yudi; Ramdani Harahap, Soritua Ahmad; Ari Anggara, Fajar Surya (IKONOMIKA, 2023)
The regulation of the Ministry of Home Affairs No. 15 of 2021 concerning PPKM had an impact on the operational decline of several important economic sectors including food and beverage, transportation, retail and also the tourism sector. No exception, micro, small and medium enterprises (MSMEs) were also affected. As a result, they have significantly decreased performance of their operational. The objective of this study is to analyses current condition of MSMEs operation in the post COVID 19 crises. A quantitative approach was employed in this study. Around 371 MSME owners were selected as sample of this study. Descriptive analysis with SPSS tools was applied as analysis technique. The results show that there is an impact of COVID 19 on the decline in the performance of MSMEs, particularly Micro and Small businesses. There is a decrease in sales turnover and profit, unavailable or expensive raw materials as well as a reduction in staff or workers. The study suggests the need for capital assistance, relaxation of loan installments and increased sales via online to help continuity of their business in facing COVID19 pandemic.